Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Di Toko Online Lazada Pada Kota Surakrta - Anita Karlina Gunawan; Anggi Septiana Sari; Rayhan Gunaningrat (Manajemen Kreatif Jurnal, 2025)
This research is useful for examining the impact of price and promotion on purchasing decisions for the Lazada e-commerce platform in the city of Surakarta. This type of research is associative with a sample of 100 individuals who have made purchases on Lazada. This research used purposive sampling techniques and primary data types, and collected data through questionnaires. Data analysis was carried out using a qualitative approach and used Multiple Linear Regression Analysis techniques, F Hypothesis Testing and t Hypothesis Testing, as well as the Coefficient of Determination. The research results show that: 1) There is an impact of price and promotions on purchasing decisions at Lazada for the city of Surakarta 2) There is an influence of price on purchasing decisions at Lazada for the city of Surakarta 3) There is an impact of promotions on purchasing decisions at Lazada for the city of Surakarta